High school student's perceptions school security - Arabaci, I. Bakir (E D P Sciences, 2016)
It is necessary to establish a secure environment for the realization of effective learning at schools. Students cannot focus on learning if they do not feel themselves in a secure environment. Today, uncontrolled change of social, cultural and technological environments poses a threat to the school security. This research aims to determine the perceptions of students studying in the high schools in Elazig and Tunceli Provinces on school security. The phenomenology design of qualitative research designs and the interview form as data the collection technique were used in the research. In this study, the qualitative research design which aims to collect in-depth information was used instead of quantitative research design. 40 students studying in the high schools in Elazig and Tunceli provinces in Turkey constitute the study group. As a result of the research, it has been revealed that the majority of female students do not feel themselves secure at school, environmental cleanliness and hygiene are not adequate at schools, and one quarter of female students and almost half of the male students are smoking.
ERPA International Congresses on Education (ERPA) -- JUN 02-04, 2016 -- Sarajevo, BOSNIA & HERCEG
Keywords: School security; high schools; school environment; student perception